Case Study - Frensya M. Nanlohy; Monica Monica (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2020)
This study is a case study research, it aims to find out how British Parliamentary debate system enhance critical thinking skills of the debaters from English Debate Club (EDC) of Pattimura University. This also leads to the extend identification and analysis of critical thinking level from EDC Debaters. The subjects are debaters from EDC who have been train educing British Parliamentary Debate System. The data was collected through In-depth interview, documents review, and audio visual materials. The result in dicates two major things that affected critical thinking from BP system, including case buildi and four teams mechanism encapsulated the effectto create platform for critical engagement in global issues to the extend analysis. As an annex, debaters can proceed to 5th level of critical thinking (Evaluation) which in dicate the 5th stages of critical thinking (Advance Thinker). Therefore, the mechanism of BP canal so be implemented in learning and teaching process, especially in critical thinking aspect.